Sahrawi Spanish: A Dialectal Characterization - Lara Bermejo, Víctor (2025)
The Spanish spoken in Western Sahara remains largely unexplored, as the few existing studies focus primarily on the language used in the refugee camps in Tindouf. This paper aims to provide a dialectal characterization of Sahrawi Spanish, based on fieldwork conducted with bilingual speakers from diverse sociolinguistic backgrounds. The findings reveal a significant influence from the phonetic system of ?ass?niyya, though this is only observed among individuals who left the African territory after a certain age. Meanwhile, the morphosyntactic phenomena observed are similar to those documented in varieties of Spanish spoken in the Iberian Peninsula.